The Rise and Fall of the Great Powers : Economic Change and Military Conflict from 1500 to 2000 - Kennedy, Paul (Lahore Services Book Club, 1996)
Examines the relationship of economic to military power as it affects the rise and fall of empires.
Include Notes, Bibliography and Index
Keywords: Military history, Modern -- History, Modern -- Economic history -- Balance of power